2019
DOI: 10.1021/acs.orglett.9b04401
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 6,12-Methanodibenzo[c,f]azocines and 4-Aryltetrahydroisoquinolines from Aromatic Aldehydes

Abstract: A methodology for the synthesis of 7,12-dihydro-5H-6,12-methanodibenzo­[c,f]­azocines from aromatic aldehydes and N-(methoxymethyl)-N-(trimethylsilylmethyl)­benzylamine using catalysis by trifluoroacetic and perchloric acids is described. The developed protocol was applied for the synthesis of N-unsubstituted and N-methyl-4-aryltetrahydroisoquinolines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…A special point of interest was an evaluation of the possibility of an intermolecular reaction of N-benzyl-5-(3,4dimethoxyphenyl)oxazolidine (3l), which is known to readily recyclize into 6,12-methanodibenzo[c,f ]azocine 4l intramolecularly. 8 To our delight, the use of veratrole as a solvent (20.0 equiv) fully shifted the reaction direction and N-benzyltetrahydroisoquinoline 5l was obtained in 79% yield (Scheme 3b). Thus, the Friedel−Crafts reaction in the studied structures is highly selective and the donation of arene again overcame the benefit of the intramolecular process.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A special point of interest was an evaluation of the possibility of an intermolecular reaction of N-benzyl-5-(3,4dimethoxyphenyl)oxazolidine (3l), which is known to readily recyclize into 6,12-methanodibenzo[c,f ]azocine 4l intramolecularly. 8 To our delight, the use of veratrole as a solvent (20.0 equiv) fully shifted the reaction direction and N-benzyltetrahydroisoquinoline 5l was obtained in 79% yield (Scheme 3b). Thus, the Friedel−Crafts reaction in the studied structures is highly selective and the donation of arene again overcame the benefit of the intramolecular process.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, we discovered an acid-promoted intramolecular recyclization of N -benzyloxazolidines 3 obtained in situ via the [3 + 2]-cycloaddition reaction of aromatic aldehydes 1 and N -(methoxymethyl)- N -(trimethylsilylmethyl)­benzylamine ( 2 ) (Scheme a) . This two-step process readily resulted in the formation of tetracyclic 6,12-methanodibenzo­[ c , f ]­azocines 4 via intramolecular domino Friedel–Crafts/Pictet–Spengler cyclizations.…”
Section: Introductionmentioning
confidence: 99%
“…[334] Buev et al demonstrated a TFA and perchloriccatalyzed protocol towards the synthesis of 4-aryltetrahydroisoquinolines 576 by taking aromatic aldehydes 174 and N-(methoxymethyl)-N-(trimethylsilylmethyl)-benzylamine 575 (Scheme 334). [335] Li et al reported a TBAB-promoted Dimroth rearrangement and successive TfOH-catalyzed reaction with electron rich arenes 539 or BF 3 -promoted reaction with aryl aldehydes 174 to access 4-aryltetrahydroisoquinolin-3-ones 579. The reaction conditions showed very good applicability on wide range of substrates by giving good to excellent yields (Scheme 335).…”
Section: Non-metal Catalyzed Isoquinoline Synthesis and Other Methodsmentioning
confidence: 99%
“…demonstrated a TFA and perchloric‐catalyzed protocol towards the synthesis of 4‐aryltetrahydroisoquinolines 576 by taking aromatic aldehydes 174 and N ‐(methoxymethyl)‐ N ‐(trimethylsilylmethyl)‐benzylamine 575 (Scheme 334). [335] …”
Section: Synthesis Of Isoquinoline Derivativesmentioning
confidence: 99%
“…There is also one example of employing p-quinol acetates as substrates for the synthesis of these compounds [17]. Recently, a methodology for the synthesis of dihydromethanodibenzoazocines based on a combination of Friedel-Crafts and Pictet-Spengler reactions was proposed by Moshkin et al [18].…”
Section: Introductionmentioning
confidence: 99%